The effectiveness of tires chips in gabion wall for slope protection - Hafiz Ashrawi, Baharun (2019)
Waste tire in Malaysia are neither categorized as solid waste or hazardous waste. It is generally consider as business or trade waste, hence currently there is no specific law or regulation, which govern waste tire management. This thesis study about the effectiveness of tire chips to use as raw material in gabion wall as slope protection. The main objective of this study is to replace the gravel in gabion wall with tire chips. This study analyzed the slope stability using various slope angle (30º, 45º and 60º), to find the critical angle due to effect of precipitation. This study also analyse the effectiveness of slope treatment using gabion filled with various proportion of 0%, 20% and 50% of tires chips in term of volume. Slope simulator model in scale 1:20 have been constructed and gabion wall were used to sustain the slope model consist of soil with 60º of critical angle. Moderate rain intensity (13mm/hour) was subjected on the slope and transducer reading that recording the displacement of gabion wall was taken. The result shows that the displacement recorded by gabion wall with 20% of tire chips and 100% gravel has a huge difference in resisting slope. Therefore, tire chips is not effective to use as alternative material for gravel in constructing of gabion wall due the large difference of displacement slope and the huge difference of specific gravity for gravel. Therefore, further study need to be constructed to studies the potential of the tire chips to be utilize in gabion wall in future.